Secondary Brown Carbon Formation From Photooxidation of Furans From Biomass Burning - T. Joo; J. E. Machesky; L. Zeng; T. Hass‐Mitchell; R. J. Weber; D. R. Gentner; N. L. Ng (Geophysical Research Letters, 2024)
Abstract Furans are a major class of volatile organic compounds emitted from biomass burning. Their high reactivity with atmospheric oxidants leads to the formation of secondary organic aerosol (SOA), including secondary brown carbon (BrC) that can affect global climate via interactions with solar radiation. Here, we investigate the optical properties and chemical composition of SOA generated via photooxidation of furfural, 2‐methylfuran, and 3‐methylfuran under dry (RH < 5%) and humid (RH ∼ 50%) conditions in the presence of nitrogen oxides (NOx) and ammonium sulfate seed aerosol. Dry furfural oxidation has the greatest BrC formation, including reduced nitrogen‐containing organic compounds (NOCs) in SOA, which are dominated by amines and amides formed from reactions between carbonyls and ammonia/ammonium. Based on the products detected, we propose novel formation pathways of NOCs in furfural photooxidation, which can contribute to BrC via accretion reactions during the photochemical aging of biomass burning plumes.